PENAMBAHAN ASAM OLEAT TERHADAP Sistem transpor Cu(II) dengan zat pembawa oksin melalui teknik membran cair fasa ruah - Tetra, Olly Norita; -, Zaharasmi; -, Refinel (Jurnal Riset Kimia, 2008)
ABSTRACT The removal of Cu(II) from aqueous solutions had been employed throught bulk liquid membrane techniques with arrange the optimization conditions of transport Cu(II) interface system. The optimum conditions of transport were found to be 3.1510-4 M of Cu(II) at pH 3  in the source phase,  17.510-4 M oxine dissolved into chloroform as membrane phase, 0,15 M H2SO4 as acceptor in  receiving phase, stirring rate was 340 rpm and  it was found that the transport of Cu(II) to receiving phase reached 97.41% during 6 hours. The effect of addition  oleat acid 1.57  10-3 M as surfactant  in membrane phase resulted a rapidly time of  transport Cu(II) to be 3 hours, wherein Cu(II) transported  into  the receive phase reached 97.83%  and remained  in feed phase 0%. Keywords: bulk liquid membrane, oxine, oleat acid, Cu(II) )transport